Absolute Isotopic Abundance Ratios and the Atomic Weight of a Reference Sample of Chromium - Shields, William R. (J Res Natl Bur Stand A Phys Chem, 1966)
Absolute values have been obtained for the isotopic abundance ratios of a reference sample of chromium, using surface emission mass spectrometry. Samples of known isotopic composition, prepared from nearly pure separated chromium isotopes, were used to calibrate the mass spectrometers. The resulting absolute values are Cr(50)/Cr(52) = 0.051859 ±0.000100, Cr(53)/Cr(52) = 0.113386 ±0.000145, Cr(54)/Cr(52) = 0.028222 ±0.000059, yielding an atomic weight (C(I2)=12) of 51.99612 ±0.00033. The indicated uncertainties arc overall limits of error based on 95 percent confidence limits for the mean and allowances for effects of known sources of possible systematic error.